2005
DOI: 10.1002/nme.1532
|View full text |Cite
|
Sign up to set email alerts
|

Generalized pointwise bias error bounds for response surface approximations

Abstract: SUMMARYThis paper proposes a generalized pointwise bias error bounds estimation method for polynomialbased response surface approximations when bias errors are substantial. A relaxation parameter is introduced to account for inconsistencies between the data and the assumed true model. The method is demonstrated with a polynomial example where the model is a quadratic polynomial while the true function is assumed to be cubic polynomial. The effect of relaxation parameter is studied. It is demonstrated that when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…There has recently been considerable attention given to RSM based approximation optimization in areas of mechanical and aerospace design optimization [2][3][4][5][6][7]. RSM is also an efficient approach that contributes to the probabilistic design such as robust and/or reliability-based design optimization [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There has recently been considerable attention given to RSM based approximation optimization in areas of mechanical and aerospace design optimization [2][3][4][5][6][7]. RSM is also an efficient approach that contributes to the probabilistic design such as robust and/or reliability-based design optimization [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional variance-based designs minimize the effect of noise and attempt to obtain uniformity (stability) over design space but they do not address bias errors. Recently Goel et al [3] have demonstrated that prediction variance is not an appropriate tool to estimate errors when bias errors are dominant.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…They assumed that the true model is a higher degree polynomial than the approximating polynomial and it satisfies the given data exactly. Goel et al [3] generalized this bias error bounds estimation method to account for inconsistencies between the assumed true model and actual data, and rank deficiencies in the matrix of equations used in linear regression. They demonstrated that the bounds can be used to develop adaptive design of experiment to reduce the effect of bias errors in region of interest.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The encouraging results from the examples indicate that it may be worthwhile studying these strategies more rigorously and in more detail. In the past, the majority of the work related to the construction of EDs was done by considering only one design objective [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. When noise is the dominant source of error, there are a number of EDs that minimize the effect of variance (noise) on the resulting approximation, for example, the D-optimal design that minimizes the variance associated with the estimates of coefficients of the response surface model.…”
mentioning
confidence: 99%